2003
DOI: 10.1016/s0378-1097(03)00442-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of strong promoter elements ofMycobacterium smegmatisand their utility for foreign gene expression in mycobacteria

Abstract: The isolation of elements driving high-level expression of foreign genes in mycobacteria would significantly aid characterization of mycobacterial antigens and recombinant vaccine development. Mycobacterium smegmatis is a widely employed host for recombinant mycobacterial gene expression. This report describes the identification of strong promoter elements of M. smegmatis. Fluorescenceactivated cell sorting was employed to isolate DNA fragments permitting high-level expression of the Aequorea victoria green fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Both pJEX57 and pMV261 were transformed into M. bovis BCG Pasteur strain 1173P2 as previously described (21). BCG strains were grown, as described previously (28), and mycobacterial cell lysates were prepared by sonication of cultures harvested at mid-log phase. The expression of mMCP-3 was verified by immunoblotting using the 12CA5 monoclonal antibody specific for the hemagglutinin epitope tag present at the N terminus of the mature protein.…”
mentioning
confidence: 99%
“…Both pJEX57 and pMV261 were transformed into M. bovis BCG Pasteur strain 1173P2 as previously described (21). BCG strains were grown, as described previously (28), and mycobacterial cell lysates were prepared by sonication of cultures harvested at mid-log phase. The expression of mMCP-3 was verified by immunoblotting using the 12CA5 monoclonal antibody specific for the hemagglutinin epitope tag present at the N terminus of the mature protein.…”
mentioning
confidence: 99%
“…These symptoms may be due to toxicity of these particular proteins, imposing heavy physiological burden on to the cells. A number of methods could be used to resolve this issue, including using plasmids with lower copy numbers, use of weaker promoters with lower expression level or using a promoter that is more tightly regulated . Alternatively, other expression hosts that are described in this manuscript could be of use.…”
Section: Expression Hosts For Mycobacterial Proteinsmentioning
confidence: 99%
“…The G13 promoter was the first mycobacterial promoter described that was highly active in an E. coli background, and others have since been described (Satchidanandam et al, 2003). Recently, Spratt et al (2003) reported that a series of strong promoters isolated from an M. smegmatis library using a similar gfp reporter system was similar to both E. coli and mycobacterial consensus promoter sequences. This same group indicated that no correlation existed between promoter sequence and strength of gfp expression.…”
Section: Analysis Of Promoter Activity In Mycobacterium Marinummentioning
confidence: 99%